Islamic Economic Thought in the Umayyad Era: A Review of the Financial and Tax Systems - Al Maulud; Khusnudin (al-Afkar, Journal For Islamic Studies, 2025)
This study focuses on the financial system and zakat in the Umayyad era from the perspective of Islamic economic thought. This study will include an analysis of the banking system applied. This study uses a literature review method to examine the financial and tax systems in the Umayyad era from the perspective of Islamic economic thought. The focus of this study lies in the use of currency, banking system, types of taxes and how they are managed. Data will be collected through relevant literature, such as books on the history of the Umayyad government, works of Islamic historians and economists, and primary sources such as historical documents and official documents of the Umayyad government. The results of this study are that the financial and zakat systems during the Umayyad era had advantages in terms of infrastructure development, good cash management, and structured banking regulations. However, there are weaknesses, such as limited regulations, many violations, and error limits. Therefore, public financial management at that time still needed improvement and refinement to increase efficiency and equity. These principles are still relevant in modern financial and tax management. Therefore, the concept of Islamic economics during the Umayyad era can be used as a valuable reference for fair and transparent financial and tax management, as well as ensuring equal distribution of income and opportunities for all members of society. These principles are still relevant today and can be a reference in the development of modern Islamic economics. Thus, the Umayyad era shows that Islamic economic principles can function well if implemented in accordance with the principles of justice, transparency, and efficiency.